2022
DOI: 10.3389/fgwh.2022.785194
|View full text |Cite
|
Sign up to set email alerts
|

Client Experiences in a Mobile-Phone Counseling Intervention for Enhancing Access to Prevention of Mother To-Child Transmission (PMTCT) Services in Kenya

Abstract: BackgroundThe prevention of mother-to-child transmission (PMTCT) is considered one of the most successful HIV prevention strategies in detecting and reducing HIV acquisition in utero or at birth. It is anticipated that with the increasing growth of digital technologies mobile phones can be utilized to enhance PMTCT services by improving provider-client interactions, expanding access to counseling services, and assisting in counteracting social and structural barriers to uptake of PMTCT services. Understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The authors further argue that such a scenario is concerning as it has negative effects on treatment outcomes, however, this was done to curb the pandemic. According to Okal et al ( 2022 ), counselling is a critical component of client management in HIV care and treatment services and should be patient-centred and meet the unique needs of each patient. Evidence has demonstrated that use of virtual counselling was an important initiative that was necessary to enhance PMTCT outcomes during COVID-19 pandemic (Okal et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors further argue that such a scenario is concerning as it has negative effects on treatment outcomes, however, this was done to curb the pandemic. According to Okal et al ( 2022 ), counselling is a critical component of client management in HIV care and treatment services and should be patient-centred and meet the unique needs of each patient. Evidence has demonstrated that use of virtual counselling was an important initiative that was necessary to enhance PMTCT outcomes during COVID-19 pandemic (Okal et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Okal et al ( 2022 ), counselling is a critical component of client management in HIV care and treatment services and should be patient-centred and meet the unique needs of each patient. Evidence has demonstrated that use of virtual counselling was an important initiative that was necessary to enhance PMTCT outcomes during COVID-19 pandemic (Okal et al 2022 ). The use of telehealth strategies observed in this study has also proved to be effective and key to enhance the continuum of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies and projects demonstrate positive impacts resulting from the use of DHIs for both infectious and noncommunicable chronic diseases (Hong & Guo, 2018;Lester, 2013;Mohammed et al, 2016). Further, DHIs are capable of enhancing systems in a much more effective and efficient manner while creating accountability compared to manual processes (Mohammed et al, 2016;Okal et al, 2016;Vojnov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, the Uptake could be better nationally at 8.5% and worse for Mombasa at 9.1%. 6 Kenya is one of the 22 countries that account for 90% of all pregnant mothers with HIV worldwide. 7 In Kenya, initiatives to reduce mother-to-child transmission (PMTCT) are seamlessly incorporated into Maternal and Child Health (MCH) services within healthcare institutions.…”
mentioning
confidence: 99%